NATIONAL UITY: SOCIAL AND CULTURAL INTEGRATION. US POPULAR CULTURE AND CONSUMERISM. PLURALISTIC INTEGRATION - Sharapova Gulshan Sharafovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article concerns about how the US became integrated socially and culturally, how Americans’ attitude was towards immigration and became more united. The formation of popular United States culture is also explored including consumerism which became commonplace during the 1920s. Moreover, the article focuses on the term “pluralistic integration” distinguishing cultural pluralism from religious pluralism.